Spin‐Orbit Torque Driven Magnetization Switching and Precession by Manipulating Thickness of CoFeB/W Heterostructures. (15th January 2020) - Kim, Changsoo; Chun, Byong Sun; Yoon, Jungbum; Kim, Dongseuk; Kim, Yong Jin; Cha, In Ho; Kim, Gyu Won; Kim, Dae Hyun; Moon, Kyoung‐Woong; Kim, Young Keun; Hwang, Chanyong
Abstract: The switching of magnetization via spin‐orbit torque has attracted much attention because of its fast switching and low power consumption. Numerous studies have focused on increasing the conversion efficiency from charge to spin current and out‐of‐plane magnetization cases. Recently, there have been reports on the fast and deterministic switching of in‐plane magnetization devices. It is reported that an in‐plane spin‐orbit torque (SOT) device can archive the oscillation, precession, and direct switching by a combination of torques—controlling the thickness of the ferromagnet and normal metal. With proper layer thicknesses, the device can show the three dynamics listed above at each current density in a macro spin simulation. Based on an understanding of the role of torque‐driving magnetization dynamics, a dynamic map of an in‐plane SOT device depending on torque efficiency and current density is shown. Abstract : Depending on the magnetic structure of the system and current densities, various types of spin dynamics such as switching, precession, and oscillation can be found. Furthermore, a dynamics map is suggested as a function of spin‐orbit torque efficiencies, which will be a guidance in the development of in‐plane spin orbit torque devices based on magnetic tunneling junctions.